2004
DOI: 10.1038/sj.ejcn.1602047
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and nutritional biomarkers in Italian type 1 diabetes families: evidence of unhealthy diet and combined-vitamin-deficient intakes

Abstract: Objective: Nutritional status and lifestyle can have profound effects on health. To analyse behaviour patterns in population subgroups of public health importance, we compared lifestyle, dietary intake of energy and selected nutrients, and nutritional biomarkers of type 1 diabetes (T1DM) patients and nondiabetic first-degree relatives against control subjects with no family history of T1DM. Design: A cross-sectional study. Setting: Department of Internal Medicine, University of Pisa, Italy. Subjects: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
15
0
2
Order By: Relevance
“…In recent years, on the contrary, the difference in BMI between unaffected siblings of type 1 diabetic probands and healthy control subjects has reached the statistical significance ( Figure 1, . This finding probably reflects the trend toward increasing body weight and obesity in the general population, declining physical activity and unhealthy dietary habits that we have documented (Matteucci et al, 2004b(Matteucci et al, , 2007(Matteucci et al, , 2008. However, the emerging difference in BMI between unaffected relatives and control subjects suggests that additional factors are operative in type 1 diabetes families, which remain unknown.…”
Section: Body Weight In Type 1 Diabetes Familiesmentioning
confidence: 78%
See 1 more Smart Citation
“…In recent years, on the contrary, the difference in BMI between unaffected siblings of type 1 diabetic probands and healthy control subjects has reached the statistical significance ( Figure 1, . This finding probably reflects the trend toward increasing body weight and obesity in the general population, declining physical activity and unhealthy dietary habits that we have documented (Matteucci et al, 2004b(Matteucci et al, , 2007(Matteucci et al, , 2008. However, the emerging difference in BMI between unaffected relatives and control subjects suggests that additional factors are operative in type 1 diabetes families, which remain unknown.…”
Section: Body Weight In Type 1 Diabetes Familiesmentioning
confidence: 78%
“…We concluded that anthropometric and anamnestic data on child and family yield more accurate estimates of risk profile: fat distribution seems relevant for metabolic and cardiovascular disorders. Since our initial investigations on type 1 diabetes families, we found that first degree relatives' BMI tended to be higher when compared with healthy control subjects who had no first-degree relative with type 1 diabetes, although the difference did not always reach statistical significance (Matteucci & Giampietro, 2000a;Matteucci et al 2004aMatteucci et al , 2004bMatteucci et al 2006). In recent years, on the contrary, the difference in BMI between unaffected siblings of type 1 diabetic probands and healthy control subjects has reached the statistical significance ( Figure 1, .…”
Section: Body Weight In Type 1 Diabetes Familiesmentioning
confidence: 96%
“…Our studies of case-families with population-based controls recruited unaffected first-degree relatives of sporadic T1D cases and population-based controls without family history of T1D [42,[44][45][46][47][48][49][50]; participants were both interviewed and provided biological material for functional biochemical characterisation. Unlike multiple-case families, our families are those less likely to carry a strong genetic predisposition.…”
Section: From the Particular (T1d Nephropathy) To The General (The Whmentioning
confidence: 99%
“…Plasma thiols (P SH), erythrocyte glutathione (RBC GSH), plasma and erythrocyte membrane malondialdehyde (P and RBC MDA), RBC NHE activity, and RBC vfcy were measured as previously reported [3][4][5][6][7]11].…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Demographic, socio-economic and lifestyle information was obtained by Lifestyle European Prospective Investigation of Cancer and Nutrition questionnaire (EPIC) [6]. Subjects reported the daily number of hours they engaged in housework and the weekly number of hours they engaged in physical activities during leisure and during work.…”
Section: Data Collectionmentioning
confidence: 99%